Situation Report: Bulgaria, 13 January 1987 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. BCP CC Plenum on Economic Reform / by Rada Nikolaev The Ninth Five Year Plan (1986-1990) / by Rada Nikolaev The BCP and the New Ideological Climate / by Stephen Ashley The BCP and the Struggle against "Negative Phenomenon" / by Stephen Ashley Anti-alcohol Campaign Intensified / by Stephen Ashley